ANALISIS ANGGARAN SEBAGAI UPAYA DALAM PERENCANAAN DAN PENGENDALIAN BIAYA PROYEK PADA PT X DI KOTA AMBON - BARUS UMARELLA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2019)
This study aims to determine and analyze the project cost budget prepared in accordance with applicable rules or not considering the allocated project cost budget is still an issue in a project development and the budget greatly influences the success of a project. The method of analysis used in this study was a Descriptive qualitative method where the data collected is based on the results of interviews with informants related to research and compares them with theories and rules relevant to the research issue. The results showed that the budget compiled did not meet the relevant requirements and theories because the budget was prepared not through discussion and socialization with the budgeting team or representatives of project members but only certain parties were involved in preparing the budget so it was clear that there were irregularities in the report realization of the budget that is not running properly.